Conflicts in Characters’ Movie of San Andreas - Adi Eka Wijaya, Kadek; Sosiowati, I Gusti Ayu Gde (Humanis; Vol 27 No 1 (2023), 2023)
The title of this study is “Conflicts in Characters’ Movie of San Andreas ”. This study deals with conflicts faced by the characters in the movie. The aims of this study are to identify the conflicts, source of conflicts, and conflict management strategies. The data was taken from movie entitled San Andreas directed by Peyton in 2015. Documentation method and note-taking technique are used to collecting data. The data were analyzed by using the theory of literature proposed by Kenney (1996), and the theory of source of conflicts by Deetz and Stevenson (1986). The result of the study showed that there are two kind of conflicts, namely internal and external conflicts